Antimycobacterial activity of Brazilian Amazon plants extracts - Lillian Lucas Carrion; Daniela Fernandes Ramos; Daiane Martins; Maria Izabel Correia Osório; Lorena de Carvalho Cursino; Denny Willian Oliveira Mesquita; Cecília Veronica Nunez; Pedro Eduardo Almeida da Silva (International Journal of Phytomedicine, 2013)
Tuberculosis (TB) is one infectious disease responsible for more than 2 million of deaths worldwide. The increase of TB cases resistant to drugs normally used in treatment has reinforced the necessity of development of new antimicrobials, which should be active to resistant strains and latent bacilli, further it should reduce the treatment duration. Thus fifty-six plants extracts obtained from Brazilian Amazon forest were tested in three strains of Mycobacterium tuberculosis, being one pan-susceptible strain (H37Rv), one isoniazid resistant and one rifampicin resistant. Twenty-nine plants extracts were active against pan-susceptible strain, twenty-four against isoniazid resistant and thirteen against rifampicin resistant. These results indicate the potential of the Brazilian Amazon plants products as source of new antimicrobials.